1999
DOI: 10.1080/096374899101445
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of food composition tables and direct chemical analysis for the assessment of macronutrient intake in a military community

Abstract: Food composition tables (FCT) were validated against chemical analysis (CA) to assess energy, carbohydrate, lipid, protein and fibre content of the food consumed by Italian Army cadets. The absolute difference between FCT and CA in 2 separate weeks was < or = 0.7% for energy, < or = 4.1% for carbohydrates, < or = 2.9% for lipids, < or = 6.2% for proteins and < or = 31.6% for fibre. It is concluded that FCT can be used to assess energy, carbohydrate, lipid and protein but not fibre intake in this military commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
1
13
0
2
Order By: Relevance
“…The same difference of 10% was considered the minimum between-place biologically relevant difference for the nutrients (CHO, CHOS, FAT, SFA, PRO, fiber, sodium and iron). Our experience in validating the 7DWFR against chemical analysis suggests that a threshold of 10% is a reasonable choice to guard against instrumental error [10,11]. To calculate sample size, we applied Monte Carlo simulation to a multivariable median regression model having E (kcal·day −1 ) as response variable and the following predictors: (1) a between-place difference of 100 kcal·day −1 of E, (2) a between-sex effect ≥20% of median E and, (3) a one-degree fractional polynomial (FP) of age modelling the continuous energy-age relationship [20,21,22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same difference of 10% was considered the minimum between-place biologically relevant difference for the nutrients (CHO, CHOS, FAT, SFA, PRO, fiber, sodium and iron). Our experience in validating the 7DWFR against chemical analysis suggests that a threshold of 10% is a reasonable choice to guard against instrumental error [10,11]. To calculate sample size, we applied Monte Carlo simulation to a multivariable median regression model having E (kcal·day −1 ) as response variable and the following predictors: (1) a between-place difference of 100 kcal·day −1 of E, (2) a between-sex effect ≥20% of median E and, (3) a one-degree fractional polynomial (FP) of age modelling the continuous energy-age relationship [20,21,22].…”
Section: Methodsmentioning
confidence: 99%
“…The 7-day weighed food-record (7DWFR) is the accepted reference method for the assessment of nutrient intake [6,7] and offers accurate estimates of macronutrient intake compared to direct chemical analysis [10,11]. A recent systematic review concluded that weighed records are needed to obtain more accurate estimates of nutrient intake in children, especially when micronutrient intake is of interest [5].…”
Section: Introductionmentioning
confidence: 99%
“…Both authors attributed the reason for the slight discrepancies to variations in food composition and to possible nutrient modi"cations which occurred during the cooking process. Bedogni et al (1999) compared the analytical composition of the meals of Italian soldiers in two di!erent weeks, with the results computed by means of food composition tables: di!erences were negligible for energy, ranging from 0.4 to 0.7% in the 2 weeks. The largest di!erence was found for "bre, where the di!erence ranged from 0 to 32%.…”
Section: Discussionmentioning
confidence: 99%
“…This is believed to be a cost-e!ective methodology. Some researchers have compared published data from food composition tables with analytical data (Porrini et al, 1986;Boulous et al, 1996;Bedogni et al, 1999), but to our knowledge no studies, to date, have tried to base such comparisons on a speci"c list of foods, selected to represent the most commonly consumed items in a country.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of meals is rare (Klicka et al, 1996). Bedogni et al (1999) compared analysed and estimated data. They reported that nutrition composition tables are suitable for estimation of energy, carbohydrates and protein but not for estimation of fibre content.…”
Section: Introductionmentioning
confidence: 99%